2008
DOI: 10.1080/00498250802001826
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of prazosin in rat and characterization of metabolites in plasma, urine, faeces, brain and bile using liquid chromatography/mass spectrometry (LC/MS)

Abstract: 1. Prazosin, 2-[4-(2-furanoyl)-piperazin-1-yl]-4-amino-6,7-dimethoxyquinazoline, is an antihypertensive agent that has been used safely since 1976 and is currently being investigated for the treatment of post-traumatic stress disorder. The in vivo metabolism of prazosin in rat was first reported in 1977, although at the time analytical techniques were not as sophisticated, nor were the mass spectrometers as sensitive, as today. Recently, the in vitro metabolism of prazosin in rat liver microsomes and cryoprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…3. Erve et al 64 reported the fragmentation pathway of prazosin that is in agreement with ours. The major structural difference is the fragment peak at 231 m/z.…”
Section: Molecules With Single Structural Domainsupporting
confidence: 90%
“…3. Erve et al 64 reported the fragmentation pathway of prazosin that is in agreement with ours. The major structural difference is the fragment peak at 231 m/z.…”
Section: Molecules With Single Structural Domainsupporting
confidence: 90%
“…Microsomes with NADPH, UGDPA or GSH as cofactors could produce oxidized metabolites as well as glucuronide and GSH conjugates, but cryopreserved hepatocytes could not produce similar amounts of GSH conjugates and glucuronide conjugate patterns were dissimilar [123]. This is consistent with reported low levels of GSH in cryopreserved hepatocytes [124].…”
Section: Examples Of In Vitro-in Vivo Extrapolationsupporting
confidence: 72%
“…The GSH conjugate was proposed to result from a reactive intermediate that could be trapped by semicarbazide [122]. Subsequent in vivo studies in rats revealed three new Phase I metabolites and a glucose and a taurine conjugate were produced in addition to previously observed in vitro metabolites [123]. In addition, one oxidated and two glucuronated metabolites were quantitatively the most abundant metabolites in vivo, but of these only the other glucuronide conjugate was quantitatively a major metabolite in in vitro incubations [123].…”
Section: Examples Of In Vitro-in Vivo Extrapolationmentioning
confidence: 96%
See 1 more Smart Citation
“…M21, the N-glucoside was unusual. Animal N-glucoside metabolites are described for barbiturates [19] and anilines [20] but quaternary N-glucosides appear to only have been previously described in plant metabolism [21]. The speculative structure drawn for imiloxan M19 was consistent with the spectral data but was unprecedented in drug metabolism.…”
Section: Time-dependent Inhibitionmentioning
confidence: 60%